Retrospective Study Analyzing Trends in Antibiotic Use in Patients with Osteomyelitis of the Ankle and Foot. Issue 1 (January 2022) - Chokshi, Shivan N.; Efejuku, Tsola; Jupiter, Daniel; Chen, Jie; Panchbhavi, Vinod K.
Category: Ankle; Hindfoot; Midfoot/Forefoot Introduction/Purpose: Antibiotic resistance has quickly become one of the most pressing current public health challenges. Many studies have analyzed general prescription trends, but little information exists about how antibiotic therapy is utilized in orthopedic practice- particularly in patients with Osteomyelitis of the Ankle and Foot. Thus, a retrospective analysis was performed using EMR data to understand temporal tends in antibiotic use, as well as the impact of patient-specific factors on antibiotic use. Methods: Patients with Osteomyelitis of the Ankle and Foot who were given antibiotics within 12 weeks of their diagnosis were identified in the EMR database using ICD 10 codes (M86.17, M86.67, M86.8X7, M86.171, M86.172, M86.27, M86.679, M86.279, M86.671, M86.672, M86.07, M86.271, M86.37) for foot and ankle Osteomyelitis and the VA Drug Classification Code (AM000) for antibiotics. We then stratified these patients by age (0-9, 10-19, 20-29, 30-39, 40-49, 50-59, 60-69, 70-79, 80-89, 90-99), gender (male, female), and year by decade (2001, 2010, 2020). In addition, pre-disposing risk factors of Osteomyelitis, such as Diabetes, Hypertension, and Chronic Ischemic Heart Disease, were analyzed for association with antibiotic use. Results: Our search identified 85, 767 patients, of whom 50, 043 (58.35%) received antibiotics within 12 weeks of Osteomyelitis diagnosis. Overall, Males (60.01%) were slightly more likely than Females (54.88%) to use antibiotics. Stratification by age revealed a skewed distribution with the highest incidence of antibiotic use seen in 50-59 year-olds (61.93%). This was more than double the incidence of antibiotic use seen among 20-29 year-olds (30.63%). Additionally, we discovered notable increases in antibiotic usage over time. The most substantial increases occurred from 2001 to 2010 (14.08% to 33.71%, respectively) and 2010 to 2020 (33.71% to 60.51%, respectively). Lastly, patients with pre-existing co-morbidities were found to have a higher usage of antibiotics, when compared to patients without the co-morbidity. Specifically, prior Hypertension increased use by 11.73%, followed by Chronic Ischemic Heart Disease (10.50% increase) and Diabetes (8.40% increase). The above differences were found to be statistically significant at a p-value of <.0001. Conclusion: This analysis provides insight into present and past antibiotic usage in patients with Foot and Ankle Osteomyelitis. Overall, patients aged 50-59, males, and with Chronic Ischemic Heart Disease are the most likely to take antibiotics within 12 weeks of their diagnosis. This is all against the background of rising antibiotic use, with notable increases since 2001. The data necessitates a deeper look into antibiotic use in patients with foot and ankle injuries as a whole.